The Relationship Between Registration Time and Outpatient Satisfaction at Dr. Tengku Mansyur Tanjungbalai Hospital - Hafidzah, Fidiana; Hasibuan, Rapotan; Agustina, Dewi (LPPM Akafarma Sunan Giri Ponorogo, 2025)
The registration unit serves as the initial point of contact in healthcare services, shaping patients’ first impressions of a hospital’s service quality. This study aimed to examine the correlation between registration service time and outpatient satisfaction at RSUD Dr. Tengku Mansyur Tanjung Balai. A quantitative research approach was utilized with a cross-sectional design and correlation analysis. A total of 105 respondents were selected through a random sampling method. Data were collected using a questionnaire adapted from prior studies and validated for reliability. The results of the Pearson correlation test showed a significant relationship between registration service time and patient satisfaction (p = 0.000). The correlation coefficient was -0.806, indicating a strong negative association. Additionally, the coefficient of determination (R²) was 0.646, which means that 64.6% of patient satisfaction was influenced by registration waiting time—categorized as a strong correlation. These findings indicate that longer registration times are associated with lower levels of patient satisfaction. The study emphasizes the importance of optimizing the registration process as a strategic step to improve overall hospital service quality.